(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The samples Eu1-xPrxBa2Cu3Oy і Eu1-xTbxBa2Cu4Oy (0£x£0,5) were synthesized by ceramic technique. The structural parameters electrophysical properties and oxygen content depend on their composition were study. The electrophysical properties depend on the type of atom REE was investigate.